Analysis Of Student’s Participation in Extracurricular Class at Sekolah Citamulia Using RFM Model - Firdaus, Aulia; Heikal, Jerry (International Journal Labs, 2024)
The cognitive development of children, as well as the academic performance of students, can be influenced by various factors. One of these factors is students' active involvement in extracurricular activities outside the classroom. These activities are supplementary programs designed to facilitate students' interests and talents in specific fields. It is crucial to maintain a high level of student participation because active participation significantly impacts cognitive and academic improvement. The objective of this study is to assess the level of active student participation by categorizing students based on their engagement using the RFM (Recency, Frequency, Monetary) method. The second objective is that, once the student engagement mapping is established, it will allow for targeted programs and policies tailored to each group, thereby enhancing overall student participation in extracurricular activities. In this RFM method, recency represents the date of the student’s most recent attendance at an activity. Frequency represents the total number of student attendances, and monetary represents the total nominal amount spent. The data was collected from January to September 2024, involving 250 students participating in extracurricular activities. Generally, the RFM output reveals student segmentation based on activity can be categorized into seven groups, which are Ashamed, Nice Tried, Bored, Initiative, Committed, Excited, and Passionate. Based on these results, several policies can be formulated according to the conditions of each student.